PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, SANKSI PERPAJAKAN, DAN PENDAPATAN MASYARAKAT TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KOTA BANJARMASIN - Ataya, Alifa Izzah Shafa; Sari, Yohana Yustika (Jurnal Riset Akuntansi Politala, 2025)
This study aims to test and analyze the effect of taxation knowledge, taxation socialization, tax sanctions, and community income on the dependent variable, namely Taxpayer Compliance in Paying Rural and Urban Land and Building Tax (PBB-P2) in Banjarmasin City. This research applies the probability sampling method with calculations using the Slovin formula. Data were collected through questionnaires. This type of research uses primary data, which is information obtained directly from the first source. The research population includes land and building taxpayers in the rural and urban sectors registered at the Banjarmasin City Financial, Revenue and Asset Management Agency (BPKPAD), with a total of 209,601 PBB-P2 taxpayers recorded. The sample in the study amounted to 400 taxpayer respondents. The analysis method used in this study is multiple linear regression using the IBM SPSS version 26 application. The results of this study indicate that tax knowledge, tax socialization, tax sanctions, and community income have a significant effect on taxpayer compliance in paying PBB-P2 in Banjarmasin City.